Photoperiod induced effects on female fecundity and egg diapause in Aedes aegypti from a temperate region of South America - Di Battista, Cristian Matias (2019)
Mosquito populations in temperate regions are confronted with unfavorable conditions such as low winter temperatures. These conditions are anticipated by a short photoperiod, which is a major cue to induce changes in the life history of insects to survive these conditions. So far, no effects of photoperiod on the female fecundity or on eggs diapause of Aedes aegypti are known, despite the fact that this species is expanding to temperate regions. Thus, the aim of the present study was to assess the effects of photoperiod on the fecundity of females and on their ability to lay diapausing eggs in a population of Ae. aegypti from a temperate region (Buenos Aires City, Argentina). To this end, we exposed both the parental generation and the eggs to short-day (SD: 10L:14D) and long-day (LD: 14L:10D) photoperiods, and studied the fecundity of females, the hatching and mortality of eggs. Egg hatching and mortality were assessed for different eggs ages (from 14 to 112 days). The individuals from the SD photoperiod showed a lower fecundity and laid eggs with lower hatching response. A trend to higher hatching with increasing egg age was recorded in all treatments. Eggs mortality was also lower in the SD photoperiod. Our results show changes in female fecundity in response to photoperiod. Furthermore, the inhibition of hatching and the lower mortality of SD eggs suggest that they are in diapause, an ability that has not been reported previously in Ae. aegypti, which would explain its expansion to temperate regions.